Soil carbon dioxide efflux from amended saline and thermally desorbed oil‐contaminated subsoil. Issue 1 (17th September 2020) - Kruger, M.; Sigdel, S.; Gasch, C.; DeSutter, T.; Harmon, J.; Chatterjee, A.
Abstract: Soil carbon (C) dynamics are often challenged by soil properties like high salt concentration and low organic matter content. To examine options for improving the quality of degraded soils, two pairs of soils, (a) non‐saline and (b) saline surface soils from an agricultural field, and (a) non‐contaminated subsoil and (b) thermal desorption‐treated subsoil from an oil‐contaminated site were collected. For the laboratory incubation, these four soils were treated with three amendments, (a) composted beef manure, (b) spent lime from sugarbeet ( Beta vulgaris L.) processing, and (c) commercial mulch (Proganics), and soil CO2 efflux was measured for three consecutive drying–rewetting (DW) cycles. Base efflux and the rate of change in base efflux were calculated from the slope and intercept of a linear fit model of CO2 efflux over time (h), respectively for each DW cycle. Soil, amendment, and DW had significant effect on base efflux and the rate of change in base efflux during DW. Proganics had the highest base efflux of 29.0 and 24.0 μg CO2 –C m −2  d −1 for saline and thermal desorption‐treated soils, respectively, and significantly ( P  < .05) higher than other amendments. Spent lime and compost also significantly ( P  < .05) increased base efflux over the control. Base efflux had a strong association with permanganate oxidizable carbon (POXC) for all soils, and a strong association with inorganic N for only saline and non‐saline soils. Amendments increased microbial metabolism and have the potential to improve soil health and crop production for soils with severe limitations.